Pengaruh Facebook Terhadap Keputusan Berkunjung Wisatawan Domestik Ke Pantai Pandawa, Bali - Pranitya, Ngurah Putu Nova Merta; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
Pandawa Beach is one of beaches that located on the south coast of Bali Island, exactly in Kutuh Village, Kuta Selatan Subdistrict, Badung - Regency. This beach is visited by hundreds of domestic tourists everyday. White sand, shallow beach, limestone hill, and also the clean torquoise water being photography or selfie objects in every single day by domestic tourists. The photos - averagely uploaded to social medias everyday. This activity surely will affect many people to come and visit to Pandawa Beach. Thus, this case made the background of choosing the topic “ Facebook’s Effect toward Visiting - Decision of Domestic Tourists to Pandawa Beach” to be researched. The goal of this research is to determine the significance of Facebook’s effect toward-visiting decision of domestic-tourists to Pandawa Beach. The research method that used - in this research are quantitative research method with validity test analysis, reliability test, frequency test, t-test, and correlation analysis to analyze the - Facebook’s effect toward visiting decision to Pandawa Beach. Data sources are gained from primary data and secondary data. Data collecting technique used observation method, documentation, and using - questionnaires. Sample of tourists determination technique used in this research is incidental sampling technique. This research is also limited with theory of planned behavior, concept of social media, concept of visiting decision, and concept of tourists. The results of this research is that - Facebook ha s effect toward the visiting decision of domestic tourists in Pandawa Beach but the effect is weak. This is caused that the tourist who visit s- Pandawa Beach also have references of another good beaches in online social media so the Pandawa Beach is not the location that prioritized or the only one tourist attraction that chosen - to be visited by domestic tourists .   Keywords : Facebook’s Effect, Visiting Decision, Domestic Tourists, Pandawa Beach